Implementasi Kompor Berbahan Bakar Sampah Untuk Kelompok PKK dan UMKM di Kelurahan Tanah Enam Ratus - Mihardi, Satria; Siregar, Alkhafi Maas; ,, Eddiyanto; Hidayat, Taufik; Fahri, Rama; Tamba, Rade Yamen; Nurlita, Nurlita; Manik, Agnes Viola; Situmorang, Immanuel Basado (Universitas Negeri Medan, 2025)
This Community Service activity aims to introduce and implement waste-fueled stove technology as an alternative energy solution for PKK groups and MSMEs in Tanah Enam Ratus Village, Medan Marelan. Through a participatory approach and hands-on training, participants were trained in utilizing household waste as fuel, efficient combustion techniques, and stove maintenance. The activity results showed an increase in participants' understanding of the concept of renewable energy and the formation of a working group